NATIVE SPEAKER TEACHERS AND TEACHING THE CULTURE OF ENGLISH - Lina Farsia (Journal Informatic, Education and Management (JIEM), 2020)
English is the world’s lingua franca which used by different people form differrent nation for communication purpose. Hence English is not only owned by the nations that use english as their first and official language but it is also owned by everyone who uses English. Every person who uses english has the same ownership of english as the person who is English native speaker. Consequently, the culture of English does not only belongs to the native english contries but also to everyone who uses english for comunication. The notion that native speaker teacher is bettter than non native speakers teachers is not valid anymore. The competence non native speakers teachers also can teach English successfully. American and British cultures are no longer the priority when it comes to teaching the culture of english but building up the awareness fo how people from different countries have different culture and improving students cross-cultural understanding is the key to the successful to the teacjing of Englishh culture